MANAGEMENT OF SEVERE HEPATIC COCCIDIOSIS IN DOMESTIC RABBITS - B. Bibin Becha; S.S. Devi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
High mortality in a period of one month due to hepatic coccidiosis was reported in a rabbit farm. Typical nodular lesions in liver and unsporulated oocysts of E. stiedai could be detected. Animals were treated with sulphaquinoxyline and diaveridine for five days followed by repetition of treatment after five days. Strict sanitary measures and disinfection of cages by spraying with 10 per cent ammonia solution was adopted. All animals with poor body conditions were removed from the flock and the disease was controlled.